4-Ethylphenol—fluxes, metabolism and excretion of a gut microbiome derived neuromodulator implicated in autism - Day, Francesca; O’Sullivan, Justin; Pook, Chris (Frontiers in Molecular Biosciences, 2023)
Gut-microbiome-derived metabolites, such as 4-Ethylphenol [4EP], have been shown to modulate neurological health and function. Although the source of such metabolites is becoming better understood, knowledge gaps remain as to the mechanisms by which they enter host circulation, how they are transported in the body, how they are metabolised and excreted, and the way they exert their effects. High blood concentrations of host-modified 4EP, 4-ethylphenol sulfate [4EPS], are associated with an anxiety phenotype in people with autism. We have reviewed the existing literature and discuss mechanisms that are proposed to contribute influx from the gut microbiome, metabolism, and excretion of 4EP. We note that increased intestinal permeability is common in people with autism, potentially explaining increased flux of 4EP and/or 4EPS across the gut epithelium and the Blood Brain Barrier [BBB]. Similarly, kidney dysfunction, another complication observed in people with autism, impacts clearance of 4EP and its derivatives from circulation. Evidence indicates that accumulation of 4EPS in the brain of mice affects connectivity between subregions, particularly those linked to anxiety. However, we found no data on the presence or quantity of 4EP and/or 4EPS in human brains, whether healthy or autism, likely due to challenges sampling this organ. We argue that the penetrative ability of 4EP is dependent on its form at the BBB and its physicochemical similarity to endogenous metabolites with dedicated active transport mechanisms across the BBB. We conclude that future research should focus on physical (e.g. ingestion of sorbents) or metabolic mechanisms (e.g. conversion to 4EP-glucuronide) that are capable of being used as interventions to reduce the flux of 4EP from the gut into the body, increase the efflux of 4EP and/or 4EPS from the brain, or increase excretion from the kidneys as a means of addressing the neurological impacts of 4EP.